2008
DOI: 10.1121/1.2968700
|View full text |Cite
|
Sign up to set email alerts
|

Self-learning active noise control

Abstract: An important step for active noise control ͑ANC͒ systems to be practical is to develop model independent ANC ͑MIANC͒ systems that tolerate parameter variations in sound fields. Reliabilities and stabilities of many MIANC systems depend on results of online system identifications. Parameter errors due to system identifications may threaten closed-loop stabilities of MIANC systems. A self-learning active noise control ͑SLANC͒ system is proposed in this study to stabilize and optimize an ANC system in case identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Detailed online secondary-path modeling algorithms and associated problems will be presented in Section III. Moreover, ANC systems that require no secondary-path models [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] will also be introduced in Section III.…”
Section: B) the Fxlms Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed online secondary-path modeling algorithms and associated problems will be presented in Section III. Moreover, ANC systems that require no secondary-path models [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] will also be introduced in Section III.…”
Section: B) the Fxlms Algorithmmentioning
confidence: 99%
“…Other ANC techniques that do not require the secon-dary-path model include methods based on the strict positive real (SPR) property of the FXLMS algorithm [62,63], adaptive genetic algorithm [64], and self-learning [65]. Among these algorithms, the SPR-based method is the most attractive owing to its simple implementation and good performance.…”
Section: New Approaches Related To Secondary-path Modelmentioning
confidence: 99%
“…Meanwhile, additive manufacturing technology has advantages in designing open-cell structures [13,14]. In recent years, sound control has been of interest to researchers, especially at low frequencies where important innovations have occurred in sound control technology such as active noise cancellation systems [15,16] and sound absorbing structures [17,18], which have gained popularity in recent decades. One of the important sound control technologies is modifying materials using nanotechnology, which has proved effective over wide bandwidths for sound control.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have suggested that many psychological stresses, chronic hearing losses and cardiovascular illnesses among the city-dwellers can be linked to excessive exposure to environmental noise [1,2]. To create a more livable city, innovations on noise control technologies, such as active noise cancellation systems [3,4] and sound absorbing structures [5,6], have undergone substantial advancement since the last decade.…”
Section: Introductionmentioning
confidence: 99%